STRENGTHENING THE CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH THE SEKAPO PROGRAM BASED ON DEEP LEARNING IN ELEMENTARY SCHOOL - Ikhsan Maulana; Nur Indah Istiqomah; Slamet Widodo; Anam Sutopo; Sutama (El Midad, 2025)
This study aims to examine and describe the strengthening of the character of elementary school students through the Sekapo Program, which means "Show a good attitude," based on deep learning at SDN 21 Kota Bima, by emphasizing the integration of local cultural values into daily learning practices. This research uses a qualitative case-study design, conducted at SDN 21, Bima City. Data collection techniques include learning observations, in-depth interviews with teachers and students, and analysis of school documents. Data analysis was carried out using Cresswell’s interactive model, which included data reduction, data presentation, and conclusions, and was tested for validity through source triangulation. The results of the study show that the Sekapo Program, based on deep learning, has strong potential as a contextual, meaningful model for strengthening students’ character. The main findings indicate improvements in students’ affective attitudes and social-emotional competence, strengthening the habituation of positive behavior and the formation of a value-oriented school culture. The integration of deep learning with local cultural values encourages the internalization of character in a more reflective and applicable manner, so that character education is not separate from the academic learning process